Legal Protection of Consumers' Personal Data in Information Technology-Based Loan and Borrowing Agreements - Sopaheluwakan, Erlin Philein; Berlianty, Teng; Pesulima, Theresia Louize (Postgraduate Program in Law, Universitas Pattimura, 2026)
Introduction: In the field of digital economy transactions, especially information technology-based loan and borrowing agreements, the importance of personal data is increasing. Even so, consumer data protection is still not adequately handled, raising concerns about the many cases of personal data breaches that actually cause losses to consumers with illegal access to consumer personal data. The birth of the Personal Data Protection Law and various regulations related to personal data protection and information technology-based lending and borrowing services is a serious step by the government to provide protection and security of consumers' personal data.Purposes of the Research: This research aims to examine and analyze the legal protection of consumers' personal data in information-based lending agreements, as well as the legal implications of the dissemination of consumers' personal data in technology-based lending agreements.Methods of the Research: The method used in this research is the normative juridical method with a legislative approach and a conceptual approach. The legal materials used are primary, secondary, and tertiary legal materials. These legal materials are analyzed qualitatively to address the issues being studied.Results Main Findings of the Research: The research results show that legal protection of consumers' personal data in technology-based lending agreements in Indonesia is currently well-regulated through Law Number 27 of 2022 on Personal Data Protection (PDP Law) and various related regulations. Although these regulations are comprehensive, their implementation still faces various challenges, particularly regarding the awareness and understanding of business actors and consumers about the importance of personal data protection. Supervision by the Financial Services Authority (OJK) and related institutions needs to be strengthened, and improvements in technology infrastructure and human resources are required to support effective implementation. Legal implications of personal data breaches affect both consumers and business actors. Consumers' rights to security and comfort are not met due to personal data breaches. Business actors who do not comply with their obligations and responsibilities regarding the protection of consumers' personal data may face various legal implications, such as loss of consumer trust, financial losses, administrative and criminal sanctions, service termination by the government, and a decrease in company value.